Influence of seedling establishment techniques and irrigation systems on growth, water use efficiency and nutrient content of rubber (Hevea brasiliensis Mull.Arg) - Nabayi, Abba (2016)
Rubber (Hevea brasiliensis) is an important crop in tropical Asian countries. In Malaysia, rubber contributes much to the economy of the country through latex production. Latex production requires seedlings that are disease-free, mature quickly and have high field survival rates. However, seedlings production in nursery is associated with the cost of irrigation water and labour. Seedlings that are less vigorous tend to spend a longer time in the field before they become established. BX-1 system (RB 900 tube and BX-1 growing media) is a new nursery planting system introduced by Humibox Sdn. Bhd. with the purpose of replacing the conventional (polybag with soil) way of raising seedlings. A research was conducted in a rain shelter at Field No.15, Faculty of Agriculture, Universiti Putra Malaysia. The treatments were: BX-1 system with sprinkler (T1), BX-1 system with drip (2), BX-1 system with capillarywick (T3) and soil-polybag with capillary wick (T4), as control. The treatments were laid in RCB design with 3 replications each and data were collected monthly for 8 months. The first objective of the research was to determine the influence of different irrigation systems on rubber seedling growth and leaf nutrient contents (N, P, K, Ca, and Mg). The results showed that the different irrigation systems had influenced the growth and leaves nutrient content significantly (P<0.01) with the higher values in the drip (T2) and capillary wick (T3) systems, and the lower values in the sprinkler system and control (soil-polybag). This was due to the higher nutrient content of the BX-1 media which is 4 times more than that in the soil. The use of BX-1 growing media would reduce mineral fertilizer application. The second objective of the research aimed at uncovering the influence of different irrigation systems in nutrient leaching loss (N, P, K, Ca, and Mg), water productivity and water use efficiency of rubber seedlings. The results indicated that the sprinkler system (T1) lost the highest amount of nutrients especially for the more mobile nutrients (such as N and K), while the control (T4) had lost the least nutrients. The lower amount of the nutrients lost in the control was due to the lower nutrient contents in the soil. Higher water productivity was recorded in drip and capillary wick irrigation systems, which differed significantly with sprinkler and control, but in terms of water use efficiency, the highest was recorded in the T4 (control) which was due to the least amount of leachate recorded in the system because of the lower hydraulic conductivity of the soil as compared with the BX-1 growing media. The third objective was to determine the cost benefit analysis between the two different growing systems (BX-1 system and soil-polybag system) of raising rubber nursery seedlings in a 100m2 area. The analysis revealed that the soil-polybag system had a total expenditure and cost-benefit saving of 92.5 and 32% respectively, over the BX-1 system in the first year, which was due to the high initial cost involved in purchasing the BX-1 system components. However, from the second year onwards, the BX-1 system will have a cost-benefit saving of 76.9 % over the soil-polybag system for a minimum period of 8 years, as many components of the BX-1 system can re-used for a minimum of 8 years. In the soil-polybag system, labour was the main challenge which accounted for more than 90% of the total cost involved in the system. In conclusion, the research showed the influence of nutrients and water in the growth of rubber seedlings, with the BX-1 systems giving the highest growth parameters. The research also confirmed that different irrigation system removes different amount of nutrients and the best irrigation system to be used in BX-1 system and soil-polybag system was the capillary wick system as it gave the lowest leachate amount compared to others. Soil-polybag system of raising rubber seedlings was the best as it saved more cost than the BX-1 system in a small scale production, but it is advisable to use BX-1 system in a large scale production as the high initial cost of the system will be recovered.